A Study of Static Var Compensation Using TSC – TCR Shunt Compensator (International Journal of Innovative Research in Engineering & Management, 2023)
The notion of reactive power management  encompasses a wide range of system and customer  challenges, particularly those connected to power quality,  because most power quality issues may be mitigated or  remedied with proper reactive power control. When strong  inductive loads are coupled to transmission lines, the  trailing load current causes a problem with power factor.  In some cases, very low current flows through the  transmission line due to minor load, resulting in a leading  parasitic capacitance in the line, resulting experience  extreme, causing the load side hand voltage must become  twice that of the sending end side voltage (Ferranti effect),  especially in long transmission system. To avoid this  problem, we developed a new hybrid reactive power  control model that uses a simultaneous combo of thyristor controlled reactor (TCR) and thyristor switched capacitor  (TSC), which will immediately include a sleek current  control spectrum from touch sensitive to deductive  approach values by varying the firing angle of the  transformer via a computer.
Keywords: Lagging load; Thyristor switched capacitor; Thyristor controlled Reactor; Reactive power